P748 Pharmacokinetics, relative bioavailability, and dose proportionality of a tablet formulation of the sphingosine 1-phosphate-1 receptor modulator VTX002 (formerly OPL-002). (30th January 2023) - Gregg, R; Yun, C; Naik, S; Huyghe, M; Harris, J; Mohan, R; Nuss, J; Sandborn, W J
Abstract: Background: VTX002 is an oral selective sphingosine 1-phosphate-1 receptor (S1P1R) modulator in clinical development for treatment of ulcerative colitis (UC). Single and multiple doses of a spray-dried dispersion (SDD) oral suspension of VTX002 were well-tolerated up to 45 mg in a phase 1 study in healthy participants and were accompanied by dose proportional reductions in lymphocyte counts, an expected pharmacodynamic outcome of treatment. 1 A separate phase 1 study compared the pharmacokinetics (PK) and pharmacodynamics of the SDD oral suspension and a tablet formulation of VTX002. Methods: Healthy adult participants (N=12) were randomised (4 per dose group) in an open-label 3-way crossover study to receive single oral doses of 5 mg or 20 mg VTX002 tablets, or 20 mg VTX002 SDD suspension followed by at least a 1-week washout between each dose as shown in Fig. 1. Study assessments included: VTX002 plasma concentrations, PK parameters, change from baseline in absolute lymphocyte count (ALC), and adverse events (AE). Results: A total of 10 participants completed the study. Mean plasma VTX002 concentrations were greatest with a single oral dose of 20 mg VTX002 SDD suspension (Fig. 2). The geometric mean peak (Cmax) and total (AUCinf ) exposure to VTX002 were lower with the 5 mg (dose normalized to 20 mg tablet) and 20 mg VTX002 tablets compared to the 20 mg VTX002 SDD suspension (Table 1). Geometric mean ratios for the tablet and SDD formulations of VTX002 are shown in Table 2. Maximum percent (SD) reduction in ALC from baseline was greatest for the 20 mg VTX002 SDD suspension and was observed at 6 hours post-dose both for the SDD suspension and the 20 mg VTX002 tablet (59.9% [11.0%] and 51.6% [9.4%], respectively). The maximum percent reduction in ALC from baseline for the 5 mg VTX002 tablet was 22.4% (9.2%) which occurred 2 hours post-dose. A total of 23 AEs were reported; of which 19 were considered mild, and 4 were moderate. Conclusion: All doses and formulations of VTX002 were well-tolerated and associated with ALC reductions. Data from this relative bioavailability study was used to convert the results from the prior phase 1 multiple ascending dose study performed with VTX002 SDD suspension to AUC equivalent tablet doses and enable tablet dose selection for phase 2. A phase 2 study of VTX002 tablets for treatment of UC is underway (ClinicalTrials.gov Identifier:NCT05156125). 1 Luo A, et al. 2020 Gastroenterology. 2020;158(6):S1188.